Specific adverse events are associated with response to exemestane therapy in postmenopausal breast cancer patients: Results from the TEAMIIA study (BOOG2006-04). Issue 4 (April 2017) - Fontein, D.B.Y.; Charehbili, A.; Nortier, J.W.R.; Putter, H.; Kranenbarg, E. Meershoek-Klein; Kroep, J.R.; Linn, S.C.; van de Velde, C.J.H.
Abstract: Purpose: In the adjuvant setting, specific adverse events (AEs) such as vasomotor symptoms (VMS) and musculoskeletal AEs are associated with relapse-free survival in aromatase inhibitor (AI)-treated patients. In the neoadjuvant setting, specific AEs may be associated with tumor response to AIs as well. Methods: Between 2007 and 2012, 107 patients participated in the prospective TEAMIIA trial, a prospective, phase II trial investigating 6 months of neoadjuvant exemestane in patients with strongly ER-positive breast cancer. Radiological response (≥30% decrease in tumor size) was studied in relation to VMSs and MSAEs. Pearson's Chi-Square tests and multivariate logistic regression analyses were used to evaluate of statistical significance (p < 0.05). Results: Out of 102 patients 26 patients (25.4%) experienced at least one episode of VMS and 27 patients (26.4%) experienced MSAE. Out of 240 reported adverse events, 71 were specific AEs (40 MSAEs, 31 VMSs). Radiological response was greater in patients who reported VMSs compared to patients who did not (70.8% vs. 49.3%, multivariate OR 2.91, 95% C.I. 1.03–8.26, P = 0.045). No significant advantage towards better response was observed in patients who experienced MSAEs (60.0% vs. 53.3%, univariate OR 1.33, 95% C.I. 0.53–3.38, P = 0.545). Conclusion: VMSs are associated with tumor response to neoadjuvant exemestane and may be useful for predicting treatment outcomes of AI treatment at an early stage in patients treated with neoadjuvant AIs.